Answer:
My answer to the question is 34.0
We can use the vertex form of a quadratic,
![y = a(x-h)^{2} + k](https://tex.z-dn.net/?f=y%20%3D%20a%28x-h%29%5E%7B2%7D%20%2B%20k)
, to find that
![g(x) = a x^{2} - 7](https://tex.z-dn.net/?f=g%28x%29%20%3D%20a%20x%5E%7B2%7D%20-%207)
. Plugging
![(x,y)](https://tex.z-dn.net/?f=%28x%2Cy%29)
ordered pairs into g(x), we see that a = 1. For example, for
![(3, 2)](https://tex.z-dn.net/?f=%283%2C%202%29)
,
![2 = a * 3^{2} - 7](https://tex.z-dn.net/?f=2%20%3D%20%20a%20%2A%203%5E%7B2%7D%20-%207)
. Solving for a gives 1.
The correct answer is C.
You can tell this by factoring the equation to get the zeros. To start, pull out the greatest common factor.
f(x) = x^4 + x^3 - 2x^2
Since each term has at least x^2, we can factor it out.
f(x) = x^2(x^2 + x - 2)
Now we can factor the inside by looking for factors of the constant, which is 2, that add up to the coefficient of x. 2 and -1 both add up to 1 and multiply to -2. So, we place these two numbers in parenthesis with an x.
f(x) = x^2(x + 2)(x - 1)
Now we can also separate the x^2 into 2 x's.
f(x) = (x)(x)(x + 2)(x - 1)
To find the zeros, we need to set them all equal to 0
x = 0
x = 0
x + 2 = 0
x = -2
x - 1 = 0
x = 1
Since there are two 0's, we know the graph just touches there. Since there are 1 of the other two numbers, we know that it crosses there.
Answer:
f(n) = -6n - 10.
Step-by-step explanation:
This is arithmetic sequence with first term a1 = -16 and common difference d = -6.
So f(n) = a1 + d(n - 1)
= -16 - 6(n - 1)
= -16 - 6n + 6
= -6n - 10.
Checking:
f(10) = -6(10) - 10 = -70.